Clinicopathological characteristics of Epstein-Barr virus and microsatellite instability subtypes of early gastric neoplasms classified by the Japanese and the World Health Organization criteria - Hiroki Tanabe; Yusuke Mizukami; Hidehiro Takei; Nobue Tamamura; Yuhi Omura; Yu Kobayashi; Yuki Murakami; Takehito Kunogi; Takahiro Sasaki; Keitaro Takahashi; Katsuyoshi Ando; Nobuhiro Ueno; et al. (Wiley, 2021)
Abstract Gastric cancer is a heterogenous disease with different phenotypes, genotypes, and clinical outcomes, including sensitivity to treatments and prognoses. Recent medical advances have enabled the classification of this heterogenous disease into several groups and the consequent analysis of their clinicopathological characteristics. Gastric cancer associated with Epstein-Barr virus (EBV) and microsatellite‐unstable tumors are considered to be the two major subtypes as they are clearly defined by well‐established methodologies, such as in situ hybridization and polymerase chain reaction‐based analyses, respectively. However, discrepancies in the histological diagnosis of gastric neoplasms remain problematic, and international harmonization should be performed to improve our understanding of gastric carcinogenesis. We re‐evaluated Japanese cases of early gastric cancer according to the current World Health Organization (WHO) criteria and classified them into genomic subtypes based on microsatellite instability (MSI) and EBV positivity to determine the initial genetic events in gastric carcinogenesis. A total of 113 Japanese early gastric cancers (including low‐ and high‐grade dysplasias) treated with endoscopic resection over 5 years were archived in our hospital. A histological re‐evaluation according to the WHO criteria revealed 54 adenocarcinomas, which were divided into 6 EBV‐positive (11.1%), 7 MSI‐high (MSI‐H, 13.0%), and 41 microsatellite stable cases (75.9%). MSI‐H adenocarcinoma was confirmed by an immunohistochemistry assay of mismatch repair proteins. Programmed death‐ligand 1 immunostaining with two antibodies (E1L3N and SP263) was positive in tumor cells of one MSI‐H adenocarcinoma case (1/7, 14.3%). The proportion of stained cells was higher with clone SP263 than with E1L3N. Histologically, EBV‐positive carcinomas were poorly differentiated (83.8%), and MSI‐H cancers were frequent in well to moderately differentiated adenocarcinoma (85.7%), indicating that the EBV‐positive subtype presented with high‐grade morphology even when an early lesion. Our study indicates that the WHO criteria are useful for subdividing Japanese early gastric cancers, and this subdivision may be useful for comparative analysis of precursor lesions and early carcinoma.